PANCASILA EDUCATION AS AN INSTRUMENT FOR SHAPING STUDENTS’ LEGAL CONSCIOUSNESS IN THE ERA OF CONSTITUTIONAL DEMOCRACY - Anshori, Ibnu; Rahmawati, Alfi Mufida (EDUCATUM: Scientific Journal of Education, 2025)
This study examines Pancasila Education as an instrument for fostering students’ legal consciousness within the context of constitutional democracy. Employing a qualitative approach with a descriptive–analytical design, the research aims to explore how Pancasila values are internalized in educational practices and how they contribute to the formation of students’ legal awareness. Data were collected through in-depth interviews, classroom observations, and document analysis, and were analyzed using a juridical–educational perspective. The findings reveal that students’ understanding of law acquired through Pancasila Education predominantly remains at a formal–normative level. Law is commonly perceived as a set of binding rules enforced by sanctions, resulting in instrumental compliance rather than value-based legal consciousness. This condition reflects the early stages of legal awareness as conceptualized by Soerjono Soekanto, in which legal knowledge and understanding have not yet developed into consistent legal attitudes and behavior. Furthermore, the study identifies a gap between the normative objectives of Pancasila Education and its pedagogical implementation. Teaching practices that rely heavily on textual and teacher-centered approaches tend to hinder the development of reflective legal awareness, echoing the critique of banking-style education proposed by Paulo Freire. The analysis also highlights the role of Pancasila Education in cultivating constitutional awareness by linking democratic values, legal responsibility, and students’ social and digital experiences. Drawing on legal culture theory by Lawrence M. Friedman and deliberative democracy theory by Jürgen Habermas, the study demonstrates that dialogical and experiential learning approaches are more effective in internalizing legal values. Overall, the findings suggest that Pancasila Education must be reoriented toward reflective, participatory, and contextual pedagogy to function as a preventive mechanism for building sustainable legal culture in a constitutional democracy.